Policy theories in hard times?: assessing the explanatory power of policy theories in the context of crisis - Wenzelburger, Georg; König, Pascal; Wolf, Frieder (Public organization review, 2019)
Can the behavior of political actors in business-as-usual conditions be analyzed with the same theoretical framework as decision-making in situations characterized by uncertainty, ambiguity, complexity and urgency? After comparing major existing approaches and evaluating their explanatory logic under crisis circumstances, the present article develops a theoretical framework which explicitly accounts for the crisis characteristics at two stages of the policy making process, agenda-setting and decision-making. The bearing of policy-entrepreneurs, international networks, institutions and partisanship on policy outcomes critically depends on the specific workings on these levels in crisis-mode. These expectations are probed in an empirical re-evaluation of the 2011 Spanish pension reform.